The Teacher’s Opinion On The Application Of Artificial Intelligence In Changing The Paradigm Of Education - Šović, Milena V. (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2025)
The general aim of this research is to investigate the attitudes of teachers in the Republic of Serbia towards the application of artificial intelligence in education, as well as to determine their level of competence in using AI tools and technologies. A specific aim of the study is to identify the challenges and barriers to the integration of AI in the classroom, as well as potential areas for improvement through professional development of teachers. To this end, a quantitative study was conducted. The sample consisted of 74 teachers working in primary, secondary and higher education institutions and universities in the Republic of Serbia. The research findings indicate that teachers recognise the benefits that artificial intelligence can bring to the educational process, but also face numerous challenges in its implementation. Key barriers include a lack of adequate training, technological infrastructure and institutional support, as well as the need to address ethical concerns and technical challenges.